The Use of the Imperialist Competitive Algorithm in Optimising the Setting of the Tram Speed Controller in the Development of a Matlab-Simulink Environment - Kolar, Vaclav; Demel, Lukas; Hrbac, Roman; Ciganek, Jiri; Zajaczek, Stanislav; Durica, Maros (Elektronika ir Elektrotechnika, 2023)
Estimating the electric power used by railway vehicles is an important factor in the planning of future power consumption, looking for possibilities to reduce the use of electric power and therefore also reduce carbon emissions. To improve the estimation, we used the imperialist competitive algorithm in the optimisation process of a mathematical model of a tram vehicle. Specifically, in the setting of the proportional and summation constant of the vehicle speed controller which emulates the activity of the driver in the simulation. Our work presents a new approach to optimising the estimation of energy consumption in tram transport. The method used is based on mathematical modelling and simulation of social development in human society. To obtain the input data for the simulation, we performed a measurement of the reference speed by means of a GPS receiver located in a sample tram vehicle. Subsequently, to verify the model and energy calculation results, we measured the output currents and voltage from the traction converter station at the corresponding time. Our method achieved a 93 % match between the measured and simulated power consumption.